Study on the welding quality in the porthole die extrusion process of aluminum alloy profiles. (2017) - Yu, Junquan; Zhao, Guoqun
Abstract: As a typical plastic deformation process with high productivity, porthole die extrusion process has been widely used to produce a variety of aluminium alloy profiles. For the profiles extruded with porthole dies, the welding quality of longitudinal weld seams is the key factor to determine their performance. In this study, different types of welding defects from millimetre scale to nanometre scale were found during porthole die extrusion by varying extrusion die structure and process parameters. Furthermore, the formation mechanisms of these welding defects were studied from both the macro and micro levels. Finally, the factors influencing the welding quality of extruded profiles were summarized. It was found that the welding quality is determined by metal flow behaviour, solid state bonding process and microstructural evolution. The formation of the un-bonded macro-defects in the extruded profile is attributed to improper metal flow behaviour, while the formation of the micro-voids on the bonding interface is caused by the insufficient solid state bonding. In addition, the metal in the welding zone usually has the particular microstructure different from the other zones, since it experiences the special thermal and mechanical history.